Comparing EFL Visual, Auditory, Kinesthetic Students’ High Learning Intensity in Increasing Speaking Performance - Dedi Aprianto; Sutarman; Lela Rahmawati (Universitas Sarjanawiyata Tamansiswa, 2025)
This study examined the impact of high learning intensity on the speaking performance of EFL students with different learning styles: visual, auditory, and kinesthetic. The study involved the 129 selected students from Computer Study Program, Bumigora University through a total sampling technique. The instruments were the VARK questionnaire identifying the participants’ learning styles, a learning intensity questionnaire assessing their learning intensity, and a speaking performance test evaluating their fluency, accuracy, pronunciation, vocabulary, and grammar. Data were analyzed by using One-Way ANOVA and Bonferroni post-hoc tests to determine differences among the groups. The findings revealed significant differences in speaking performance across the three learning styles with F value 59.967, Sig. value 0.000 < 0.05. Kinesthetic learners demonstrated the highest mean score of 82.16), significantly outperforming visual learners’ mean score of 77.09, and auditory learners’ mean score of 70.80. Post-hoc analysis confirmed that kinesthetic learners performed significantly better than auditory learners with mean difference is 11.364, Sig. value 0.000 < 0.05, and visual learners’ mean difference is 5.069, Sig. value 0.000 < 0.05. The visual learners also outperformed auditory learners with mean difference is 6.295, Sig. value 0.000 < 0.05. These results suggested that the kinesthetic learners benefited most from the high-intensity learning environments, achieving better speaking performance. This study showed the importance of considering learning styles in designing EFL learning curriculum. The findings emphasize the need for integrating kinesthetic activities into instructional practices to maximize speaking performance, particularly in high-intensity learning contexts.